2022
DOI: 10.2174/0929866529666220426122432
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Expression, Purification and PEGylation of DNA Ligases

Abstract: Background: Reagent proteins such as DNA ligases play a central role in the global reagents market. DNA ligases are routinely used and are vital in academic and science research environments. Their major functions include sealing nicks by linking the 5’-phosphorylated end to a 3’-hydroxyl end on the phosphodiester backbone of DNA, utilizing ATP or NADP molecules as an energy source. Objective: The current study sought to investigate the role of PEGylation on the biological activity of purified recombinant DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Other groups on TPPs can also be utilized as potential sites for PEGylation, such as amino acid residues located at the protein or peptide's C-terminus (Cazalis et al, 2004), glycosylation sites consisting of serine and threonine residues (Giorgi et al, 2014), and histidine residue (Wylie et al, 2001;Zuma et al, 2022b;Zuma et al, 2022a;Khataminezhad et al, 2023). Both IFN α-2b and IFN β-1b were fused to the Mycobacterium xenopi GyrA intein and expressed in Escherichia coli.…”
Section: Site-specific Modifications Of the Other Groupsmentioning
confidence: 99%
“…Other groups on TPPs can also be utilized as potential sites for PEGylation, such as amino acid residues located at the protein or peptide's C-terminus (Cazalis et al, 2004), glycosylation sites consisting of serine and threonine residues (Giorgi et al, 2014), and histidine residue (Wylie et al, 2001;Zuma et al, 2022b;Zuma et al, 2022a;Khataminezhad et al, 2023). Both IFN α-2b and IFN β-1b were fused to the Mycobacterium xenopi GyrA intein and expressed in Escherichia coli.…”
Section: Site-specific Modifications Of the Other Groupsmentioning
confidence: 99%
“…Residue specific PEGylation was shown to strengthen the Glu12-Arg14 salt-bridge by shielding it from the interference of water molecules [ 22 ]. Recently, Zuma and colleagues (2022) recently demonstrated that site-specific PEGylation enhances the biological activity and stability of recombinant DNA ligase proteins [ 23 ]. Cooper and colleagues showed that proteins treated with mono-sulfone-PEG retained higher significantly conjugation [ 24 ].…”
Section: Site-specific Protein Pegylation Strategiesmentioning
confidence: 99%